A Study on Impact of Pesticides on Vegetables and Fruits - Padhi, S K; Khamari, Bhagyashree (International Journal of Psychosocial Rehabilitation, 2025)
For food production, pesticides are commonly used to increase food security despite the fact that on consumers, they have negative health effects. Pesticides are also harmful to plants and most food crops, including vegetables and fruits, after washing and peeling, contain residues of pesticides. The pesticides are highly poisonous and these pesticides can lead to the death of humans and animals even in very small quantities, whereas exposure to a sufficient quantity of almost any pesticide can cause long-term disease. One of the most common ways of exposure to pesticides in consumers is through the consumption of food. Like other plants, during production and storage, vegetables and fruits are attacked by the pests and diseases that results in damage which decreases the yield and the quality.During the cultivation of crops, pesticides are used along with the other pest management methods to kill pests and prevent diseases in order to diminish the loss and sustain the quality of fruit and vegetable harvest. The purpose of this study is to explain the occurrence of pesticide residues in vegetables and fruits, primarily how they dissipated, influenced by the techniques of food processing and their risk assessment.